INCORPORATING FUZZY GRAPHIC MATROID IN NETWORK CONSTRUCTION USING INDEX CODES - Shanmugavel, Saranya; R., Buvaneswari (ShodhKosh: Journal of Visual and Performing Arts, 2024)
A fuzzy graphic matroid can be represented over a finite field F. The neccesary and sufficient conditions of a fuzzy graphic matroid to be binary are given. Also, discussed the fuzzy graph-theoretic context in which fuzzy matroids arise. Fuzzy matroid operations, which will illuminate more analogies that corresponds to the operations in fuzzy graph theory and matrix theory. The traditional network models stores the received packets and forward them without applying any additional process to the packets. The uncertainties caused during the transmission of messages in the traditional network models are rectified and noiseless trans- mission of messages in the network model is improved. The primary emphasis of this paper lies in the exploration of network codes and their correlation with fuzzy graphic matroid.